REALITAS YANG RELASIONAL: CATATAN TEOLOGIS TERHADAP KERUSAKAN LINGKUNGAN - Samosir, Leonardus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2007)
The destruction of nature will keep going on if humans do not change their worldview. Reality should be viewed as an interrelated unity. Only in such worldview that the anthropocentric-dominative culture, with its utilitariantendency – the main cause of the destruction- can be overcome.